Konzeption eines Lernzirkels zu experimentellen Kompetenzen - Goertz, Simon; Klein, Patrick; Riese, Josef; Heinke, Heidrun (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Kiel 2018)

Die Veränderung physikdidaktischen Wissens im Lehr-Lern-Seminar - Joswig, Ann-Kathrin; Riese, Josef (Naturwissenschaftliche Bildung als Grundlage für berufliche und gesellschaftliche Teilhabe. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Kiel 2018)

Performance-Oriented Testing and Training in Teacher Education - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Reinhold, Peter; Schecker, Horst; Buschütter, David; Enkrott, Patrick; Kempin, Maren; Schröder, Jan (Student Learning Outcomes Assessment in Higher Education – Perspectives, Concepts and Approaches for Research, Transfer and Implementation (KoKoHs Working Papers, 12))

Development of Prospective Physics Teachers’ Pedagogical Content Knowledge While preparing for an Internship - Joswig-Käfer, Ann-Kathrin; Riese, Josef (E-Book Proceedings of the ESERA 2019 Conference: The beauty and pleasure of understanding: engaging with contemporary challenges through science education)

Assessing Student Teachers‘ Skills to plan Physics Lessons - Schröder, Jan; Vogelsang, Christoph; Riese, Josef (E-Book Proceedings of the ESERA 2019 Conference: The beauty and pleasure of understanding: engaging with contemporary challenges through science education)

Didaktische Rekonstruktion der Beschleunigerphysik und Entwicklung eines Lehr-Linearbeschleunigers - Bechstein, Stefan; Stahl, Achim; Riese, Josef (PhyDid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung 2019 in Aachen)

Veränderung des physikdidaktischen Wissens im Verlauf eines Lehr-Lern-Seminars - Joswig, Ann-Kathrin; Riese, Josef (PhyDid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung 2019 in Aachen)

Professionswissen von Physiklehramtsstudierenden in Österreich - Krumphals, Ingrid; Riese, Josef (Forschungsperspektiven 11: Lehrerinnen und Lehrerbildung in der Sekundarstufe)

Water adsorption and capillary bridge formation on silica micro-particle layers modified with perfluorinated organosilane monolayers - Giner, Ignacio; Torun, Boray; Han, Yan; Duderija, Belma; Meinderink, Dennis; Orive, Alejandro González; de los Arcos de Pedro, Maria Teresa; Weinberger, Christian; Tiemann, Michael; Schmid, Hans-Joachim; Grundmeier, Guido (Applied Surface Science)
Monodisperse micron-sized silica particle monolayers deposited onto plasma-grown SiOx-ultra-thin films have been used as reference systems to investigate wetting, water adsorption and capillary bridge formation as a function of silica surface functionalization. 1H,1H, 2H,2H perfluorooctyltriethoxysil (FOTS) monolayers, have been deposited on the respective surfaces by means of chemical vapor deposition resulting in macroscopically low energy surfaces. X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared (FTIR) reflection absorption spectroscopy confirmed the monolayer formation. Water adsorption isotherms were studied by a combination of in-situ FTIR reflection spectroscopy and quartz crystal microbalance (QCM) while macroscopic wetting was analysed by contact angle measurements. The comparative data evaluation indicates that the macroscopic wetting behaviour was changed as expected, however, that water nanodroplets formed both at intrinsic defects of the FOTS monolayer and at the FOTS/SiOx interface. Capillary bridges of liquid water are dominantly formed in the confined particle contact areas and between surface asperities on the particles. The comparison of wetting, adsorption and capillary bridge formation shows that the hydrophobization of porous materials by organosilane monolayers leads to the formation of morphology dependent nanoscopic defects that act as sites for preferential capillary bridge formation.

Entwicklung von Einstellungen, Selbstwirksamkeitserwartungen und Stressbewertung in Bezug auf Inklusion bei angehenden Sportlehrkräften –Vorläufige Ergebnisse einer hochschuldidaktischen Interventionsstudie - Grimminger-Seidensticker, Elke; Lautenbach, F. (Professionalisierung in der Sportlehrer*innenbildung – Konzepte und Forschungen im Rahmen der Qualitätsoffensive Lehrerbildung)

Emprise normative et déprise suggérée : des inégalités sociales dans l’injonction au vieillir actif en Europe - Grimminger-Seidensticker, Elke; Aceti, M.; Vieille Marchiset, G.; Knobé, S. (Figures du vieillir et formes de déprise)

Körperunzufriedenheit, Angsterleben und Präferenzen didaktischer Inszenierungen im Sportunterricht der Grundschule - Grimminger-Seidensticker, Elke; Korte, J.; Möhwald, Aiko Julia; Trojan, J. (Zeitschrift für sportpädagogische Forschung)

Excited‐State Kinetics of an Air‐Stable Cyclometalated Iron(II) Complex - Steube, Jakob; Burkhardt, Lukas; Päpcke, Ayla; Moll, Johannes; Zimmer, Peter; Schoch, Roland; Wölper, Christoph; Heinze, Katja; Lochbrunner, Stefan; Bauer, Matthias (Chemistry – A European Journal)

Creativity in data analysis through confrontation with anomalous data - Pollmeier, Pascal; Fechner, Sabine (The beauty and pleasure of understanding: engaging with contemporary challenges through science education. Electronic Proceedings of the ESERA 2019 Conference.)
Creativity is perceived to be one of the core competences to succeed in the modern world. It is connected to art, music, dancing, etc., but there is just little insight into the role of creativity in science. As data analysis plays a major role in science, creative thinking has to be used to form theories out of observations. This study uses models-of-data to represent the mental model of the students. Within models-of-data different observations and previous knowledge are linked through different types of links, e.g. causal links. The goal of this study was to examine the creative aspect of data evaluation in presence of anomalous data. The students were confronted with two experiments which contradicted each other with regard to the underlying theory. Afterwards the students were asked to decide about their favored theory and reasoning about their choice in their lab reports. The model-of-data, which was reconstructed from the lab reports of the students, was used to extract creative aspects in the mental modelling process. Furthermore, a pre-post-questionnaire on epistemological beliefs of the students was conducted. Students mostly acquired an unscientific view on epistemology in school. The question was whether the confrontation with anomalous data and the triggering of creative modelling processes have any influence on this. The results show that most students did not take anomalous data into account in their modelling processes. They did either not recognise or just ignore the data. Just a few students worked on their theory because of the new, contradictory data. The students working on their theory scored higher in the post-questionnaire, so a positive effect of creativity on scientific epistemology can be assumed. Thus, creativity obviously gets a part of science and should be taught in school science in order to make students aware of their own creative potential.
Keywords: epistemology; conceptual change; anomalous data

Effector-specific priming effects during action observation in combat sports. - Polzien, Andrea; Güldenpenning, Iris; Weigelt, Matthias (German Journal of Exercise and Sport Research)

Processing head fakes in basketball: Are there ironic effects of instructions on the head-fake effect in basketball? - Güldenpenning, Iris; Weigelt, Matthias; Kunde, Wilfried (Human Movement Science)

NRW-Sportschule: eine Längsschnittstudie zu Freizeitaktivität, chronischem Stress und Selbstkonzept - Breithecker, Jennifer; Kehne, Miriam (Zeitschrift für sportpädagogische Forschung)

Motorische Basiskompetenzen - Strotmeyer, Anne; Kehne, Miriam; Herrmann, Christian (German Journal of Exercise and Sport Research)
In der Sportwissenschaft existiert eine Vielzahl von motorischen Testinstrumenten, deren Konstruktionen unterschiedliche Zielstellungen verfolgen. Mit MOBAK-3-4 (Motorische Basiskompetenzen) etabliert sich ein kompetenzorientiertes Testverfahren für Dritt- und Viertklässler. In der vorliegenden Untersuchung mit N = 344 Kindern (167 Mädchen; M = 8,78 Jahre, SD = 0,40) sollen die faktorielle Validität des MOBAK-3-4 Testinstruments sowie Zusammenhänge mit dem Geschlecht, Alter und Gewichtsstatus (Body Mass Index, BMI), der Häufigkeit und Art von außerschulischer Sportaktivität sowie dem fähigkeitsorientierten Hagedorn-Parcours aufgeklärt werden. Die zweifaktorielle Struktur des MOBAK-3-4 konnte mit den Faktoren Sich-Bewegen und Etwas-Bewegen bestätigt werden (CFI = 0,97; RMSEA = 0,033). Zusammenhänge mit den motorischen Basiskompetenzen konnten durch die Integration der Kovariaten Geschlecht, Alter und BMI sowie Häufigkeit und Art von außerschulischer Sportaktivität in die konfirmatorische Faktorenanalyse nachgewiesen werden. Jungen zeigten gegenüber Mädchen im Umgang mit dem Ball (Etwas-Bewegen) bessere Leistungen. Mädchen waren hinsichtlich der Ganzkörperkoordination im Raum (Sich-Bewegen) leicht überlegen. Während die älteren Kinder im Etwas-Bewegen stärker als die jüngeren Kinder waren, zeigten sich im Sich-Bewegen keine altersspezifischen Leistungsunterschiede. Weiterhin stand die Häufigkeit Mannschaftssport in einem engen Zusammenhang mit Etwas-Bewegen sowie die Ausübung von Individualsportarten mit Sich-Bewegen. Zudem zeigten die Ergebnisse des Hagedorn-Parcours auf latenter Ebene mittlere bis starke Zusammenhänge mit den Kompetenzbereichen Sich-Bewegen (β = 0,75, p < 0,001) und Etwas-Bewegen (β = 0,66, p < 0,001).

Effects of Acute Physical Exercise With Low and High Cognitive Demands on Executive Functions in Children: A Systematic Review - Paschen, Linda; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatric Exercise Science)
Purpose : Whereas many studies addressed the relation between acute physical exercise and executive functions (EF) in children, the effects of various modalities of acute exercise on EF still remain unclear. This systematic review investigated the effects of exercise with low and high cognitive demands on speed of processing and accuracy of performance in tasks examining inhibition, working memory, and cognitive flexibility in children. Method : A systematic literature research in electronic databases was performed. Controlled trials assessing the effects of acute exercise on EF in a pre–post design were included. Results : Ten studies involving a total of 890 participants revealed positive effects in working memory performance in speed of processing after acute exercises with low cognitive demands compared with seated rest, mixed results for inhibition after exercises with low and high cognitive demands, and mixed results for cognitive flexibility with low cognitive demands. Concerning accuracy, only mixed results were found for inhibition after exercises with low and high cognitive demands. Conclusion : The differentiated effects of acute exercises with low and high cognitive demands led to more positive effects in speed of processing compared with accuracy of performance. Further investigations including assessment of neurophysiological parameters of EF are needed.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; Pediatrics; Perinatology and Child Health

Effects of Acute Physical Exercise With Low and High Cognitive Demands on Executive Functions in Children: A Systematic Review. - Paschen, Linda; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatr Exerc Sci)